PENGARUH KONFLIK PERAN, AMBIGUITAS PERAN, KELEBIHAN PERAN DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERASI: Studi Empiris Pada Pegawai Kantor Pelayanan Pajak Pratama Yogyakarta - Thomy Prima Arumsari; Suci Utami Wikaningtyas (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The purpose of this study was to test and analyze the effect of role conflict, role ambiguity, role excess and work stress on work productivity with emotional intelligence as a moderating variable for employees at KPP Pratama Yogyakarta. This research is a quantitative descriptive research. The method in this research is a quantitative descriptive method with a correlational research approach. The population in this study were 105 KPP Pratama Yogyakarta employees. The sampling technique used is saturated sampling technique. The data collection technique used was field research or field studies, in which researchers directly distributed questionnaires to respondents and analyzed the data using the Structural Equation Model (SEM). The results of this study indicate that . role conflict has no effect on work productivity, role ambiguity, role excess and work stress have an effect on work productivity, role conflict and role ambiguity have an effect on work productivity moderated by emotional intelligence and role excess and work stress have no effect on work productivity moderated by emotional intelligence. In addition, emotional intelligence affects work productivity.